Boogie [videorecording (DVD)] - Huang, Eddie, 1982-; Takahashi, Taylor; Paige, Taylour, 1990-; Yung, Perry (Universal Pictures Home Entertainment, 2021)
Alfred "Boogie" Chin, a basketball phenom living in Queens, N.Y., dreams of one day playing in the NBA. While his parents pressure him to focus on earning a scholarship to an elite college, Boogie must find a way to navigate a new girlfriend, high school, on-court rivals, and the burden of expectation.